Spy Satellites - Kupperberg, Paul (New York : Rosen Pub. Group, 2003)
Examines the history, technology, and uses of spy satellites, looking especially at the various reconnaissance satellite programs of the United States, from the mid-twentieth century to the present.
A cold war in space -- CORONA -- Inside a spy satellite -- Eyes in the sky.
Keywords: Space surveillance -- United States; Space surveillance